Intermittent Fasting: A Potential Effective Strategy for Preventing Obesity and Type II Diabetes Mellitus - Sam Walker; Angela M. Tacinelli; Hexirui Wu; Sarah Pendergraft; Karla Horsfall; Sami Dridi (Advances in Food Technology and Nutrition Sciences, 2018)
The prevalence of obesity among adults has increased signifi-cantly in the past few decades. In the US alone, one in three adults is classified as obese.1 Most commonly, obesity results from an imbalance of limited energy expenditure to compensate for excess energy intake.